Designing an educational game "Cleantopia" to increase students' awareness of environmental cleanliness at Mekarsari Elementary School - Ramadhan, Riki; Simanjuntak, Eva Riris; Fallah, Liana; Padmasari, Ayung Candra (Jurnal Inovasi Teknologi Pendidikan, 2024)
In general, knowledge of the types of waste in Indonesia still needs to be improved. This is one-factor causing problems in Indonesia's waste management system. The importance of knowing the kinds of waste must start from childhood. With the child's good memory, the knowledge can be absorbed more efficiently so that the application in the surrounding environment can run optimally. This research aims to increase students' awareness of environmental cleanliness at school. The object studied is taking samples from class 4A students of Mekarsari Elementary School using the Multimedia Development Life Cycle (MDLC) method. Based on the data processing results from respondents, the results obtained show that this educational game application, 'Cleantopia,' can run well and attract students' attention. In addition, with this application, students become aware of cleanliness in their school through observations made by researchers of student activities that become more orderly in disposing of garbage in its place and maintaining classroom cleanliness.